THE OPTIMIZATION OF DIABETES MELLITUS PREVENTION EDUCATION IN PONDOK MELATI SUB-DISTRICT - Junengsih junengsih; Yusuf Nasirudin; Christina Natalia Devina; Yudhia Fratidina; Fauzia Yulfitria; Mardeyanti Mardeyanti (Jurnal Pengabdian Masyarakat Fisioterapi dan Kesehatan Indonesia, 2023)
Diabetes is the leading cause of blindness, heart attacks, stroke, kidney failure and foot amputations. With early prevention efforts, 80% of cases of diabetes can be prevented. The education is aimed at raising public awareness of the disease itself, acute and chronic DM complications and its prevention, as well as other management through routine blood sugar monitoring and DM disease management. In order to improve the knowledge and understanding of the elderly about hypertension and diabetes, one of the efforts made is to provide health education on hypertensive and diabetic diseases, as well as screening of the community in particular the elders in the district of Pondok Melati. by Bekasi. As for the stage of community service activities, this includes the preparation stage: approach to the people, meetings with Camat Pondok Melati, inventory and prioritize the handling of problems, make a schedule of settlement and take action to advance the agreement decided jointly. The second is the stage of implementation that includes education with the material: understanding of classification, signs and symptoms, complications, stimulation and physical exercise for the prevention of diabetes.The method of execution that is performed in the activity of service to the community, is by performing the service. In other words, provide knowledge about the prevention efforts of diabetes mellitus disease in the district of Pondok Melati Bekasi. The activities of implementation of devotion in the community began with anamnesies, blood sugar levels examination and discharge. To evaluate the process, there is enthusiasm and feedback from the target. And the evaluation results are done after the dissemination activity is completed. Implementation of the prevention of diabetes mellitus education in the district of Pondok Melati Bekasi, all participants as many as 37 people can follow the activities well so that the participants experience improvement of knowledge and attitude.